Synergistic action on microorganisms of complex of essential oils with other biocides - Pirog, Tatiana; Kliuchka, Igor; Kliuchka (Nykytyuk), Lilia (My University, 2019)
This review summarizes the published data and own results concerning synergism of antimicrobial activity of essential oils with antibiotics against bacteria of the family Enterobacteriaceae, genera Staphylococcus, Pseudomonas, Acinetobacter; with synthetic antifungal drug fluconazole, against yeast genus Candida; with surfactants of microbial origin, against bacterial and yeast test cultures. The synergistic effect of the complex of essential oils with antibiotics, enzymes, surfactants, etc. on biofilms was considered as well. Mixing essential oils with other biocides allowed to significantly decrease the minimum inhibitory concentrations of each component. The probability of emerging resistance to antibiotics was also reduced in the pathogenic bacteria and yeasts due to the antimicrobial action of essential oils that caused the dysfunction of cellular membrane of microorganisms. The prospects of implementing complex essential oils with antibiotic nisin in the food industry, and with other antibiotics in veterinary medicine are discussed. В огляді узагальнено опубліковані дані та власні результати щодо синергізму антимікробної дії ефірних олій з антибіотиками проти бактерій родини Enterobacteriaceae, родів Staphylococcus, Pseudomonas, Acinetobacter; з синтетичним протигрибковим препаратом флуконазолом, проти дріжджів роду Candida; з поверхнево-активними речовинами мікробного походження, проти бактеріальних і дріжджових тест-культур. Розглянуто також синергічний вплив комплексу ефірних олій з антибіотиками, ферментами, поверхнево-активними речовинами тощо на біоплівки. Змішування ефірних олій з іншими біоцидами дозволило значно знизити мінімальні інгібуючі концентрації кожного компонента. Вірогідність виникнення резистентності до антибіотиків була також знижена у патогенних бактерій і дріжджів завдяки антимікробній дії ефірних олій, які викликали дисфункцію клітинної мембрани мікроорганізмів. Обговорено перспективи впровадження комплексних ефірних олій з антибіотиком низином у харчову промисловість, а з іншими антибіотиками – у ветеринарію.
Keywords: ефірні олії; антимікробна дія; синергізм; біоплівки; кафедра біотехнології і мікробіології; essential oils; antimicrobial effect; synergism; biofilms